The research and application of intelligent fault diagnosis methods - HE Yong; LI Zeng-fang (浙江大学学报. 农业与生命科学版)
The main point of intelligent fault diagnosis theory is fault mode distinguish principle based on data processing methods. Data processing methods mainly include wavelet analysis, main component analysis and rough theory. Fault diagnosis theory mainly includes expert system fault diagnosis, fussy fault diagnosis, grey mode fault diagnosis, neural network fault diagnosis, data fusion fault diagnosis and CBR fault diagnosis. The principle and application of each method are introduced and analyzed. Finally, the development trends of fault diagnosis theory are presented.